IMPLEMENTASI LESSON STUDY SEBAGAI UPAYA PENINGKATANKOMPETENSI PEDAGOGIK GURU EKONOMI DI KABUPATEN KEPULAUAN MERANTI. (Proceeding 7th International Seminar on Regional Education, 2015)
AbstractThis research was aimed to determinethe lesson study implementation to increase pedagogical competence of economics teacher in Kepulauan Meranti Regency. Samples were taken by purposive, namely economics teacher has and has not implement the lesson study in their school.The data was collected through documentation, observation, and interviews, and analyzed through descriptive qualitative. The research findings the implementation of lesson study had a positive impact to increase pedagogical competence of economics teacher. After implementing lesson study, the ability of economics teachers in designing lesson plans increased to either category with score of 91. So also in implementing learning activities in the classroom get score of 90. The impact of the implementation of lesson study for learners found as many as 89.5 percent said learning activities into more active, fun and exciting.Keywords: lesson study implementation, pedagogical competence of economics teacher